Phát hiện lần đầu tiên khoáng vật Jonassonite - AuBi5S4 ở Việt Nam - Borisenko, A. S.; Hòa, Trần Trọng; Vasilev, V. I.; Morsev, N. K.; Vấn, Vũ Văn; Phượng, Ngô Thị; Thành, Hoàng Hữu; Anh, Trần Tuấn; Dung, Phạm Thị (Vietnam Journal of Earth Sciences, 2008)
The first discovery of Jonassonite in Vietnam